2011
DOI: 10.1016/j.virol.2011.03.001
|View full text |Cite
|
Sign up to set email alerts
|

A membrane-associated movement protein of Pelargonium flower break virus shows RNA-binding activity and contains a biologically relevant leucine zipper-like motif

Abstract: Two small viral proteins (DGBp1 and DGBp2) have been proposed to act in a concerted manner to aid intra- and intercellular trafficking of carmoviruses though the distribution of functions and mode of action of each protein partner are not yet clear. Here we have confirmed the requirement of the DGBps of Pelargonium flower break virus (PFBV), p7 and p12, for pathogen movement. Studies focused on p12 have shown that it associates to cellular membranes, which is in accordance to its hydrophobic profile and to tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 72 publications
0
11
0
3
Order By: Relevance
“…benthamiana and C . quinoa leaves were obtained by phenol extraction and LiCl precipitation [ 36 ]. In addition, for RNA stability assays, protoplasts were collected at 1 and 3 h after inoculation and total RNA was extracted using NucleoZOL reagent according the manufacturers instructions (Macherey-Nagel).…”
Section: Methodsmentioning
confidence: 99%
“…benthamiana and C . quinoa leaves were obtained by phenol extraction and LiCl precipitation [ 36 ]. In addition, for RNA stability assays, protoplasts were collected at 1 and 3 h after inoculation and total RNA was extracted using NucleoZOL reagent according the manufacturers instructions (Macherey-Nagel).…”
Section: Methodsmentioning
confidence: 99%
“…In other words, the leucine zipper motif facilitates dimerization through parallel coiled-coil motifs and binds DNA through its hydrophobic domain. In more recent publications, this motif is no longer considered to be restricted to DNA binding but is generally accepted as a protein-protein interaction domain (24,32). To illustrate the domain in pUL71, we presented aa 34 to 55 in an alpha-helical wheel (data not shown).…”
Section: Fig 2 Oligomerization Potential Of Rpul71 (A)mentioning
confidence: 99%
“…Reverse genetics experiments have shown that both proteins are required for viral replication [24]. Two small ORFs, located in the central part of the viral genome, encode polypeptides of 7 (p7) and 12 kDa (p12), respectively, which are involved in virus movement [25] and the 3′-proximal ORF encodes a 37 kDa product (p37) which plays a dual role as coat protein (CP) and as suppressor of RNA silencing [26].…”
Section: Introductionmentioning
confidence: 99%